Field Multiathlon as Part of Special Physical Training of Preinductions - Oleh Dykyi (Lesya Ukrainka Volyn National University, 2016)
Topicality of the research is predetermined by available contradictions between the demands of society in preparing young people of preinduction age for defending the homeland and a strong tendency towards deterioration of the health of young men, their lack of physical training to perform military duty. The purpose of the reseach - to theoretically justify the feasibility of elective courses with militarysports-around in the system of high school extracurricular activities. The results of the work. In ensuring the efficiency of physical education of high school students diversification of extracurricular activities, such as a military application heptathlon, is of great importance. The purpose of this military-applied sport - preparing young people of preinduction age for military service and homeland defense. The main task - raising moral and psychological stability, a sense of patriotism and collectivism of future Defenders, preventing antisocial manifestations among young people, to develop and promote a healthy lifestyle, increased physical activity, enhancing the prestige of military service, to attract young people to systematic physical culture and sports. Conclusions. Thus, during the informative glut of school programs by basic disciplines, deterioration of educational material base of preiduction training, lack of motor activity of seniors, low use of modern technologies of motor activity in the classroom we see the follofing solution of the problem: field multiathlon in extracurricular activities that will allow to consolidate efforts and attract young people to the military-patriotic activities, significantly improve physical culture in future for their willingness to serve in the Armed forces of Ukraine.